Weekend Tourism - a Tourism Product aimed at Customers Living and Working in Big Cities in Vietnam - Xuan Thi Hong Phan (Journal of Entrepreneurship and Business, 2020)
To implement this article, we have chosen the research area of Binh Duong (bordering Ho Chi Minh City, with a history of over 300 years of development, with 11 years of operating the type of weekend tourism from 2008 to present); have used some research methods in social sciences, particularly ethnographic fieldwork such as strategic interview, comparing and analyzing data gathered from multiple sources. The article consists of three parts: The concept of "Weekend tourism" and specific products; Identify key factors affecting the exploitation of the "weekend tourism" type in Binh Duong, and finally, a number of measures to contribute to the development of "weekend tourism" in the context of international integration.